Meta-analysis of prophylactic abdominal drainage in pancreatic surgery. Issue 6 (20th March 2017) - Hüttner, F J; Probst, P; Knebel, P; Strobel, O; Hackert, T; Ulrich, A; Büchler, M W; Diener, M K
Abstract: Background: Intra-abdominal drains are frequently used after pancreatic surgery whereas their benefit in other gastrointestinal operations has been questioned. The objective of this meta-analysis was to compare abdominal drainage with no drainage after pancreatic surgery. Methods: PubMed, the Cochrane Library and Web of Science electronic databases were searched systematically to identify RCTs comparing abdominal drainage with no drainage after pancreatic surgery. Two independent reviewers critically appraised the studies and extracted data. Meta-analyses were performed using a random-effects model. Odds ratios (ORs) were calculated to aggregate dichotomous outcomes, and weighted mean differences for continuous outcomes. Summary effect measures were presented together with their 95 per cent confidence intervals. Results: Some 711 patients from three RCTs were included. The 30-day mortality rate was 2·0 per cent in the drain group versus 3·4 per cent after no drainage (OR 0·68, 95 per cent c.i. 0·26 to 1·79; P = 0·43). The morbidity rate was 65·6 per cent in the drain group and 62·0 per cent in the no-drain group (OR 1·17, 0·86 to 1·60; P = 0·31). Clinically relevant pancreatic fistulas were seen in 11·5 per cent of patients in the drain group and 9·5 per cent in the no-drain group. Reinterventions, intra-abdominal abscesses and duration of hospital stay also showed no significant difference between the two groups. Conclusion: Pancreatic resection with, or without abdominal drainage results in similar rates of mortality, morbidity and reintervention. Abstract : No benefit